Pengaruh Model Hybrid TGFU-TPSR terhadap Kreativitas dan Sikap Sportivitas Siswa SD - Moh Said Usman; Agus Mahendra; Wildan Alfia Nugroho (Universitas Hamzanwadi, 2026)
Physical Education, Sports, and Health instruction in elementary schools still tends to focus on the repetitive mastery of techniques, resulting in suboptimal development of students’ creativity and sportsmanship. This study aims to analyze the effect of a hybrid model combining Teaching Games for Understanding (TGFU) and Teaching Personal and Social Responsibility (TPSR) based on invasion games on the creativity and sportsmanship of elementary school students. The method used was an experiment with a one-group pretest-posttest design. The sample consisted of 30 fifth-grade students from Nur El Hikmah Elementary School, selected through purposive sampling. Creativity was measured using the Thinking Creatively in Action and Movement (TCAM) instrument, while sportsmanship was measured using the Multidimensional Sportspersonship Orientation Scale (MSOS). Data were analyzed using a paired-sample t-test. The results showed a significant increase in creativity from 21.80 to 25.83 (p < 0.05) and in sportsmanship from 56.73 to 60.30 (p < 0.05). In conclusion, the hybrid TGFU and TPSR models based on invasion games are effective in simultaneously enhancing elementary school students’ creativity and sportsmanship. This study provides an empirical contribution to the development of an integrated, contextual, and relevant physical education learning model that meets the needs of 21st-century education.